A sodium-ion battery cell, battery device, and power-using device
Patent Information
- Application Number
- CN202511292069.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-10
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-09-10
AI Technical Summary
但是随着金属锂资源的储量减少和开采难度加大,目前的金属锂资源已无法匹配锂电池产业的需求
[0004] This application is made in view of the above-mentioned issues, and its purpose is to provide a sodium-ion battery cell, battery device and power device that still have better life performance when subjected to high-rate discharge at room temperature or low temperature.
Smart Images

Figure CN121583988B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a sodium-ion battery cell, a battery device, and an electrical device. Background Technology
[0002] In recent years, with the gradual development and application of lithium-ion batteries from portable electronic devices to high-power electric vehicles, large-scale energy storage power stations, and smart grids, the demand for metallic lithium has been increasing across various industries. However, with the depletion of metallic lithium reserves and the increasing difficulty of mining, current metallic lithium resources can no longer meet the needs of the lithium battery industry. Sodium, which belongs to the same group as lithium, has similar chemical properties to lithium and is abundant. Therefore, sodium-ion batteries, which operate on a similar principle to lithium-ion batteries, are currently being developed, with the expectation that they will serve as an important supplement to lithium-ion batteries in large-scale energy storage applications.
[0003] Therefore, how to ensure that sodium-ion batteries can maintain their lifespan performance while discharging at high rates is an urgent problem to be solved. Summary of the Invention
[0004] This application is made in view of the above-mentioned issues, and its purpose is to provide a sodium-ion battery cell, battery device and power device that still have better life performance when subjected to high-rate discharge at room temperature or low temperature.
[0005] To achieve the above objectives, this application provides a sodium-ion battery cell, a battery device, and an electrical device.
[0006] The first aspect of this application provides a sodium-ion battery cell, including an electrolyte, a negative electrode, and a positive electrode; wherein the positive electrode includes a positive current collector and a positive electrode film, the positive electrode film is disposed on at least one side of the positive current collector, and the thickness L of the positive electrode film on one side of the positive current collector satisfies: 55μm≤L≤125μm, the positive electrode film includes sodium phosphate and a carbon coating material, the carbon coating material coating at least a portion of the surface of the sodium phosphate; the electrolyte includes a cyclic carbonate, a chain ester, and an additive; the freezing point F of the cyclic carbonate satisfies: -60℃≤F≤38℃, the viscosity N of the chain ester at 25±1℃ satisfies: 0.2mPa.s≤N≤3mPa.s, the mass ratio E of the cyclic carbonate and the chain ester satisfies: 0.06≤E≤1.47, the additive includes a difluorooxalate borate compound, and the mass percentage A of the additive in the electrolyte satisfies: 0.05%≤A≤2%.
[0007] Optionally, L satisfies: 55μm≤L≤85μm.
[0008] Alternatively, E satisfies: 0.14≤E≤0.93.
[0009] Optionally, A satisfies: 0.1% ≤ A ≤ 1%.
[0010] In the embodiments of this application, when the thickness of the positive electrode film is within the aforementioned range and the surface of the sodium phosphate salt is carbon-coated, the positive electrode sheet can have a higher sodium ion transport rate and electronic conductivity, thereby improving the high-rate discharge performance of the sodium-ion battery cell. Furthermore, when the electrolyte contains low-freezing-point cyclic carbonates, it can improve the liquid-phase transport rate of sodium ions in the electrolyte at low temperatures, while also improving the stability of the electrode / electrolyte interface film. Simultaneously, introducing low-viscosity chain esters into the electrolyte can improve the migration kinetics of sodium ions while simultaneously considering sodium salt dissociation, thus increasing the discharge power of the sodium-ion battery cell. Within the aforementioned ratio range of cyclic carbonates and chain esters in the electrolyte, a better balance can be struck between sodium salt dissociation and improved sodium ion migration kinetics, allowing sodium ions in the electrolyte to reach the positive electrode interface more quickly to participate in the reaction. Combining the above technical solutions, under low-temperature conditions, sodium ions extracted from the negative electrode active material can more quickly pass through the electrolyte to reach the positive electrode interface to participate in the reaction, thereby enabling the sodium-ion battery cell to still have higher discharge power under conditions of poor power, such as low temperature / low charge. Meanwhile, during the charging and discharging process of sodium-ion battery cells, difluorooxalate borate compounds, as electrolyte additives, can further reduce side reactions at the electrode / electrolyte interface. This allows sodium-ion battery cells to maintain higher discharge power even under poor power conditions such as low temperature / low charge, while also ensuring the lifespan performance of sodium-ion battery cells.
[0011] In some embodiments, the mass percentage E1 of the cyclic carbonate in the electrolyte satisfies: 0.05 ≤ E1 ≤ 0.5.
[0012] In the embodiments of this application, when the mass percentage of cyclic carbonate in the electrolyte is within the above-mentioned range, the sodium salt can be better dissociated, thereby improving the stability of the negative electrode / electrolyte interface film.
[0013] In some embodiments, the mass percentage E2 of the chain ester in the electrolyte satisfies: 0.4 ≤ E2 ≤ 0.9.
[0014] In the embodiments of this application, when the mass percentage of the chain ester in the electrolyte is within the above-mentioned range, the migration kinetics of sodium ions can be further improved, thereby increasing the discharge power of the sodium-ion battery cell.
[0015] In some embodiments, the average thickness H of the carbon coating material on at least a portion of the surface of the sodium phosphate salt satisfies: 0.4 nm ≤ H ≤ 10 nm. Optionally, 2 nm ≤ H ≤ 5 nm.
[0016] In the embodiments of this application, the average thickness of the carbon coating material on the surface of the sodium phosphate salt is within the above-mentioned range, which can increase the contact area between the positive electrode active material and the electrolyte, thereby improving the sodium ion transport kinetics between the positive electrode active material and the electrolyte.
[0017] In some embodiments, the general formula for sodium phosphate is Na. x Fe y (PO4) m (P2O7) n , where 3≤x≤5, 1.5≤m≤2.5, -0.15≤(nm) / 2≤0.15, 1.95≤[(4n+3m)-x] / y≤2.1.
[0018] In some embodiments, the Dv50 of the sodium phosphate salt satisfies: 1 μm ≤ Dv50 ≤ 18 μm. Optionally, the Dv50 satisfies: 7 μm ≤ Dv50 ≤ 11 μm.
[0019] In the embodiments of this application, the sodium phosphate particle size is within the above-mentioned range, which can improve the power performance of sodium-ion battery cells while taking into account the life performance of sodium-ion batteries.
[0020] In some embodiments, the sodium phosphate salt includes sodium iron pyrophosphate and / or sodium iron pyrophosphate.
[0021] In the embodiments of this application, the sodium ion migration potential barrier in sodium iron pyrophosphate is low, and sodium iron pyrophosphate and sodium iron phosphate can form a heterostructure, thereby improving the sodium ion diffusion capacity inside the positive electrode active material, reducing charge transfer impedance, and improving the power performance of sodium ion battery cells.
[0022] In some embodiments, cyclic carbonates include propylene carbonate and / or ethylene carbonate.
[0023] In the embodiments of this application, the relevant components of the cyclic carbonate can also be decomposed into a film to a certain extent to improve the interfacial stability of the electrode / electrolyte, thereby further taking into account the life performance of the sodium-ion battery cell.
[0024] In some embodiments, the chain esters include chain carbonates and / or chain carboxylic acid esters.
[0025] In the embodiments of this application, the relevant components of the chain ester can further enhance the sodium ion migration kinetics under low temperature conditions, thereby improving the low-temperature discharge power of sodium ion battery cells.
[0026] In some embodiments, the sodium-ion battery cell further includes: a housing, which is a hollow structure with an opening, and the electrolyte, negative electrode, and positive electrode are housed within the housing; and a top cover that closes the opening.
[0027] A second aspect of this application provides a battery device including a sodium-ion battery cell from the first aspect of this application.
[0028] A third aspect of this application provides an electrical device, including a sodium-ion battery cell of the first aspect of this application and / or a battery device of the second aspect of this application.
[0029] In some implementations, the sodium-ion battery cell or battery device is powered by a start-stop power supply for an electrical device. Attached Figure Description
[0030] Figure 1 This is a schematic diagram of the structure of a sodium-ion battery cell according to one embodiment of this application.
[0031] Figure 2 This is a schematic diagram of a sodium-ion battery cell according to one embodiment of this application.
[0032] Figure 3 This is a schematic diagram of a battery module according to one embodiment of this application.
[0033] Figure 4 This is a schematic diagram of a battery device according to one embodiment of this application.
[0034] Figure 5 yes Figure 4 An exploded view of a battery device according to an embodiment of this application is shown.
[0035] Figure 6 This is a schematic diagram of an electrical device in which a single battery cell is used as a power source according to one embodiment of this application.
[0036] Explanation of reference numerals in the attached figures:
[0037] 1 Battery assembly; 2 Upper housing; 3 Lower housing; 4 Battery module; 5 Sodium-ion battery cell; 51 Negative electrode; 52 Separator; 53 Positive electrode. Detailed Implementation
[0038] The following detailed description, with appropriate reference to the accompanying drawings, specifically discloses embodiments of the electrode plates, battery cells, battery modules, battery devices, and power-consuming devices of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0039] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0040] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0041] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0042] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0043] In recent years, with the gradual development and application of lithium-ion batteries from portable electronic devices to high-power electric vehicles, large-scale energy storage power stations, and smart grids, the demand for metallic lithium has been increasing across various industries. However, with the depletion of metallic lithium reserves and the increasing difficulty of mining, current metallic lithium resources can no longer meet the needs of the lithium battery industry. Sodium, which belongs to the same group as lithium, has similar chemical properties to lithium and is abundant. Therefore, sodium-ion batteries, which operate on a similar principle to lithium-ion batteries, are currently being developed, with the expectation that they will serve as an important supplement to lithium-ion batteries in large-scale energy storage applications.
[0044] During their research on the performance of sodium-ion batteries, the applicant discovered that, under high-power discharge requirements, the smaller phosphate particle size of phosphate cathode active materials, compared to high-temperature environments, can accelerate sodium ion migration at room temperature or low temperatures due to the shortened ion transport path, thus achieving high-power discharge. However, during the charge and discharge process of sodium-ion batteries, the significant volume changes of small-particle-size phosphate materials may lead to particle breakage and structural collapse, thereby affecting the capacity performance of the phosphate cathode active material and reducing the cycle life performance of the sodium-ion battery. Some related technologies can meet the charge and discharge capacity requirements by heating the battery system; however, this may increase the complexity of the battery system design. Other related technologies can improve cycle and storage performance by increasing the phosphate particle size; however, this increases the ion transport path and affects high-power discharge performance. Therefore, in some related technologies, the charge transfer between the positive electrode active material and the electrolyte can be improved by using large-particle-size phosphate and low-viscosity, high-conductivity electrolyte. This allows for improved capacity performance with large-particle-size phosphate while also maintaining high-power discharge performance. However, in these technologies, the solvent components of the low-viscosity, high-conductivity electrolyte have poor reduction stability and may react with the phosphate positive electrode active material, affecting the cycle performance and storage performance of sodium phosphate batteries.
[0045] The applicant recognized that the main bottleneck restricting the aforementioned problems lies in the severe polarization caused by impaired charge transfer at the interface between the positive electrode and the electrolyte, especially during high-current charge and discharge. When a sodium-ion battery cell exceeds a certain polarization voltage, it cannot maintain high-rate capacity output, macroscopically manifested as a rapid drop in the positive electrode potential in the discharge curve. In cases of severe polarization, the local potential of the positive electrode may exceed the stability window of the electrolyte, potentially leading to side reactions between the positive electrode active material and the electrolyte, forming a passivation film that further hinders electron and ion transport. Furthermore, the positive electrode may suffer irreversible structural or chemical damage, further reducing the performance and lifespan of the sodium-ion battery cell. In summary, the bottleneck for the lifespan performance of phosphate-based sodium-ion battery cells at high-rate discharge in room temperature or low-temperature scenarios lies in how to reduce the interfacial impedance between the positive electrode and the electrolyte while minimizing the impact of electrolyte side reactions on lifespan performance.
[0046] To reduce the interfacial impedance between the positive electrode and the electrolyte, the applicant recognized that current improvements in the electronic conductivity of phosphate positive electrode materials are limited. Therefore, while controlling the graphitization degree of the phosphate carbon coating to improve the electronic conductivity of the phosphate positive electrode active material, it is also necessary to use a low-temperature, high-conductivity electrolyte to accelerate the migration rate of ions at the positive electrode / electrolyte interface under low-temperature conditions, reduce ion accumulation at the interface, lower the polarization voltage, and alleviate the increase in charge transfer impedance, thereby improving the high-power discharge performance of sodium phosphate batteries under low-temperature conditions. Furthermore, the applicant also recognized the need to simultaneously suppress side reactions between electrolyte solvent components and the phosphate positive electrode active material to reduce the negative impact of these side reactions on the cycle performance and storage performance of sodium phosphate batteries.
[0047] In view of this, embodiments of this application provide a sodium-ion battery cell, including an electrolyte, a negative electrode, and a positive electrode; wherein, the positive electrode includes a positive current collector and a positive electrode film, the positive electrode film being disposed on at least one side of the positive current collector, and the thickness L of the positive electrode film on one side of the positive current collector satisfies: 55μm≤L≤125μm, the positive electrode film includes sodium phosphate and a carbon coating material, the carbon coating material coating at least a portion of the surface of the sodium phosphate; the electrolyte includes cyclic carbonate, chain ester, and additives. The freezing point F of the cyclic carbonate satisfies: -60℃≤F≤38℃. The viscosity N of the chain ester at 25±1℃ satisfies: 0.2mPa.s≤N≤3mPa.s. The mass ratio E of the cyclic carbonate and the chain ester satisfies: 0.06≤E≤1.47. The additive includes a difluorooxalate borate compound, and the mass percentage A of the additive in the electrolyte satisfies: 0.05%≤A≤2%.
[0048] Based on the above understanding, the applicant, in designing the positive electrode, has a relatively thin positive electrode film layer while maintaining the energy density of the battery cell, which can improve the transport rate of sodium ions in the positive electrode. Furthermore, carbon coating the surface of the sodium phosphate salt can further improve the electronic conductivity of the positive electrode active material.
[0049] Meanwhile, in the electrolyte design for use with the aforementioned positive electrode, the cyclic carbonate in the electrolyte can dissociate from the sodium salt and has a lower freezing point, thereby improving the liquid-phase transport rate of sodium ions in the electrolyte at low temperatures. Simultaneously, the cyclic carbonate can be decomposed into a film, optimizing the electrode / electrolyte interface, thus further improving the stability of the positive electrode / electrolyte interface film without affecting the sodium ion migration rate. Furthermore, the introduction of low-viscosity chain esters into the electrolyte can improve the sodium ion migration kinetics while simultaneously ensuring sodium salt dissociation, thereby enhancing the low-temperature discharge power of the sodium-ion battery cell. In summary, within the aforementioned ratio range of cyclic carbonate and chain esters in the electrolyte, a better balance between sodium salt dissociation and improved sodium ion migration kinetics can be achieved, allowing sodium ions in the electrolyte to reach the positive electrode interface more quickly to participate in the reaction under low-temperature conditions. Meanwhile, during the charge and discharge process of a sodium-ion battery cell, difluorooxalate borate compounds, as electrolyte additives, can decompose on the surface of the positive electrode to form a thin and stable CEI film, reducing side reactions between the phosphate positive electrode active material and the electrolyte solvent components, thereby reducing the impact on the capacity decay of the sodium-ion battery. Simultaneously, difluorooxalate borate compounds can also form a thin and stable SEI film on the surface of the negative electrode, further reducing side reactions at the electrode / electrolyte interface, thus facilitating the charge transfer process at the electrode interface and further improving the cycle performance and storage life of the sodium-ion battery.
[0050] In summary, the above-described technical solution combining the positive electrode and the electrolyte allows sodium ions extracted from the negative electrode active material to reach the positive electrode interface more quickly via the electrolyte and participate in the reaction, while also exhibiting fewer side reactions at the negative electrode / electrolyte interface. Therefore, the sodium-ion battery cell based on the phosphate system provided in this application still exhibits better lifespan performance when subjected to high-rate discharge at room temperature or low temperature.
[0051] The sodium-ion battery cell, battery module, battery, and power-consuming device of this application are described below with appropriate reference to the accompanying drawings.
[0052] Typically, a sodium-ion battery cell includes a positive electrode, a negative electrode, an electrolyte, and a separator. During charging and discharging, active ions move back and forth between the positive and negative electrodes, inserting and extracting. The electrolyte acts as a conductor between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits while allowing ions to pass through.
[0053] [Sodium-ion battery cell]
[0054] In one embodiment of this application, a sodium-ion battery cell 5 is proposed. Figure 1 This is a schematic diagram of the structure of a sodium-ion battery cell according to an embodiment of this application. The sodium-ion battery cell 5 includes a negative electrode 51, a separator 52, a positive electrode 53, and an electrolyte. The positive electrode 53 includes a positive current collector and a positive electrode film layer. The positive electrode film layer is disposed on at least one side of the positive current collector. The thickness L of the positive electrode film layer on one side of the positive current collector satisfies: 55 μm ≤ L ≤ 125 μm. The positive electrode film layer includes sodium phosphate and a carbon coating material. The carbon coating material covers at least a portion of the surface of the sodium phosphate.
[0055] Optionally, L satisfies: 55μm≤L≤85μm.
[0056] L can be 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, 100μm, 105μm, 110μm, 115μm, 120μm, 125μm or any value within the above range.
[0057] Specifically, the positive electrode film layer is disposed on at least one side of the surface of the positive electrode current collector. As an example, the positive electrode current collector may have two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.
[0058] Specifically, the carbon-coated material coating at least a portion of the surface of the sodium phosphate salt can be either a portion of the surface surrounded by the carbon-coated material or all surfaces of the sodium phosphate salt completely encapsulated by the carbon-coated material. As an example, in the positive electrode film layer, sodium phosphate salt partially surrounded by carbon-coated material and sodium phosphate salt completely encapsulated by carbon-coated material can coexist, or only sodium phosphate salt partially surrounded by carbon-coated material can exist, or only sodium phosphate salt completely encapsulated by carbon-coated material can exist.
[0059] In positive electrode design, a thinner positive electrode film layer can improve the transport rate of sodium ions within the positive electrode while maintaining the energy density of the individual battery cells. Furthermore, carbon coating the surface of sodium phosphate can further enhance the electronic conductivity of the positive electrode active material.
[0060] The electrolyte comprises cyclic carbonates, linear esters, and additives. The freezing point F of the cyclic carbonates satisfies: -60℃ ≤ F ≤ 38℃. The viscosity N of the linear esters at 25±1℃ satisfies: 0.2 mPa·s ≤ N ≤ 3 mPa·s. The mass ratio E of cyclic carbonates to linear esters satisfies: 0.06 ≤ E ≤ 1.47. Additives include difluorooxalate borate compounds, and the mass percentage A of the additives in the electrolyte satisfies: 0.05% ≤ A ≤ 2%.
[0061] Alternatively, E satisfies: 0.14≤E≤0.93.
[0062] Optionally, A satisfies: 0.1% ≤ A ≤ 1%.
[0063] F can be -60℃, -55℃, -50℃, -45℃, -40℃, -35℃, -30℃, -20℃, -15℃, -10℃, 25℃, 38℃, or any value within the above range. N can be 0.2 mPa·s, 0.5 mPa·s, 1 mPa·s, 1.5 mPa·s, 2 mPa·s, 2.5 mPa·s, 3 mPa·s, or any value within the above range. E can be 0.06, 0.1, 0.14, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.46, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.93, 0.95, 1, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.47, or any value within the above range. A can be 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, or any value within the above range.
[0064] In electrolyte design, cyclic carbonates in the electrolyte can dissociate sodium salts and have lower freezing points, thus improving the liquid-phase transport rate of sodium ions in the electrolyte at low temperatures. Simultaneously, cyclic carbonates can be decomposed into films to optimize the interfacial stability of the electrode / electrolyte interface, thereby further improving the stability of the positive electrode / electrolyte interfacial film without affecting the sodium ion migration rate. Furthermore, the introduction of low-viscosity chain esters into the electrolyte can improve sodium ion migration kinetics while simultaneously ensuring sodium salt dissociation, thereby increasing the discharge power of sodium-ion battery cells. In summary, within the aforementioned ratio range of cyclic carbonates and chain esters in the electrolyte, a better balance between sodium salt dissociation and improved sodium ion migration kinetics can be achieved, allowing sodium ions in the electrolyte to reach the positive electrode interface more quickly to participate in the reaction. Meanwhile, during the charge and discharge process of a sodium-ion battery cell, difluorooxalate borate compound, as an electrolyte additive, can decompose on the surface of the positive electrode to form a thin and stable CEI film, reducing side reactions between the phosphate positive electrode active material and the electrolyte solvent components. It can also form a thin and stable SEI film on the surface of the negative electrode, thereby further reducing side reactions at the electrode / electrolyte interface. This, in turn, is beneficial to the charge transfer process at the electrode interface, further improving the discharge power performance, cycle performance, and storage life of the sodium-ion battery under low-temperature conditions.
[0065] In the embodiments of this application, when the thickness of the positive electrode film is within the aforementioned range and the surface of the sodium phosphate salt is carbon-coated, the positive electrode sheet can have a higher sodium ion transport rate and electronic conductivity, thereby improving the high-rate discharge performance of the sodium-ion battery cell. Furthermore, when the electrolyte contains low-freezing-point cyclic carbonates, it can improve the liquid-phase transport rate of sodium ions in the electrolyte at low temperatures, while also improving the stability of the electrode / electrolyte interface film. Simultaneously, introducing low-viscosity chain esters into the electrolyte can improve the migration kinetics of sodium ions while simultaneously considering sodium salt dissociation, thus increasing the discharge power of the sodium-ion battery cell. Within the aforementioned ratio range of cyclic carbonates and chain esters in the electrolyte, a better balance can be struck between sodium salt dissociation and improved sodium ion migration kinetics, allowing sodium ions in the electrolyte to reach the positive electrode interface more quickly to participate in the reaction. Combining the above technical solutions, under low-temperature conditions, sodium ions extracted from the negative electrode active material can more quickly pass through the electrolyte to reach the positive electrode interface to participate in the reaction, thereby enabling the sodium-ion battery cell to still have higher discharge power under conditions of poor power, such as low temperature / low charge. Meanwhile, during the charging and discharging process of sodium-ion battery cells, difluorooxalate borate compounds, as electrolyte additives, can further reduce side reactions at the electrode / electrolyte interface. This allows sodium-ion battery cells to maintain higher discharge power even under poor power conditions such as low temperature / low charge, while also ensuring the lifespan performance of sodium-ion battery cells.
[0066] The content of organic components (such as solvents or organic additives) in the above-mentioned electrolytes can be tested qualitatively and quantitatively by gas chromatography, referring to the methods in GB / T6041-2002 and GB / T 9722-2006. The content of salts and salt-type additives in the above-mentioned electrolytes can be tested by referring to the General Rules for Ion Chromatography in the General Rules for Analytical Methods of Modern Analytical Instruments (JY / T 020-1996, issued on January 23, 1997, and implemented on April 1, 1997).
[0067] In some embodiments, the general formula of the difluorooxalate borate compound is (F₂C₂O₄B). y M y+ , of which M y+ Including Li + Na + K + 、Rb + Cs + Mg 2+ Ca 2+ Ba 2+ Fe 2+ Ni 2+ Al 3+ Fe 3+ Ni 3+ One or more of the following, where y = 1, 2 or 3.
[0068] In some embodiments, the mass percentage E1 of the cyclic carbonate in the electrolyte satisfies: 0.05 ≤ E1 ≤ 0.5. Optionally, E1 satisfies: 0.1 ≤ E1 ≤ 0.4.
[0069] E1 can be 0.05, 0.1, 0.15, 0.2, 0.25, 0.26, 0.3, 0.35, 0.4, 0.45, 0.5 or any value within the above range.
[0070] In the embodiments of this application, when the mass percentage of cyclic carbonate in the electrolyte is within the above-mentioned range, the sodium salt can be better dissociated, thereby improving the stability of the negative electrode / electrolyte interface film.
[0071] In some embodiments, the mass percentage E2 of the chain ester in the electrolyte satisfies: 0.4 ≤ E2 ≤ 0.9. Optionally, E2 satisfies: 0.5 ≤ E2 ≤ 0.8.
[0072] E2 can be 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9 or any value within the above range.
[0073] In the embodiments of this application, when the mass percentage of the chain ester in the electrolyte is within the above-mentioned range, the migration kinetics of sodium ions can be further improved, thereby increasing the discharge power of the sodium-ion battery cell.
[0074] In some embodiments, the average thickness H of the carbon coating material on at least a portion of the surface of the sodium phosphate salt satisfies: 0.4 nm ≤ H ≤ 10 nm. Optionally, 2 nm ≤ H ≤ 5 nm.
[0075] H can be 0.4nm, 0.5nm, 1nm, 1.5nm, 2nm, 2.5nm, 3nm, 3.5nm, 4nm, 4.5nm, 5nm, 5.5nm, 6nm, 6.5nm, 7nm, 7.5nm, 8nm, 8.5nm, 9nm, 9.5nm, 10nm or any value within the above range.
[0076] The average thickness of the carbon coating material on the sodium phosphate surface may affect the contact area between the positive electrode active material and the electrolyte, thereby potentially influencing the sodium ion transport kinetics between them. If the average thickness of the carbon coating material is too thick, the contact area between the positive electrode active material and the electrolyte may be too small, potentially reducing the sodium ion transport kinetics between them.
[0077] In the embodiments of this application, the average thickness of the carbon coating material on the surface of the sodium phosphate salt is within the above-mentioned range, which can increase the contact area between the positive electrode active material and the electrolyte, thereby improving the sodium ion transport kinetics between the positive electrode active material and the electrolyte.
[0078] The average thickness of the aforementioned carbon-coated material on the sodium phosphate surface can be observed using a transmission electron microscope.
[0079] In some embodiments, the general formula for sodium phosphate is Na. x Fe y (PO4) m (P2O7) n , where 3≤x≤5, 1.5≤m≤2.5, -0.15≤(nm) / 2≤0.15, 1.95≤[(4n+3m)-x] / y≤2.1.
[0080] x can be 3, 4, 5, or any value within the range mentioned above. m can be 1.5, 2, 2.5, or any value within the range mentioned above.
[0081] In some embodiments, the Dv50 of the sodium phosphate salt satisfies: 1 μm ≤ Dv50 ≤ 18 μm. Optionally, the Dv50 satisfies: 7 μm ≤ Dv50 ≤ 11 μm.
[0082] Dv50 can be 1μm, 5μm, 7μm, 10μm, 11μm, 15μm, 18μm or any value within the above range.
[0083] Larger particle sizes of sodium phosphate can improve the cycle performance and storage performance of sodium-ion battery cells. However, excessively large particle sizes of the positive electrode active material may also increase the sodium-ion transport path, potentially reducing the discharge power performance of the sodium-ion battery cell.
[0084] In the embodiments of this application, the sodium phosphate particle size is within the above-mentioned range, which can improve the power performance of sodium-ion battery cells while taking into account the life performance of sodium-ion batteries.
[0085] In some embodiments, the sodium phosphate salt includes sodium iron pyrophosphate and / or sodium iron pyrophosphate.
[0086] Specifically, sodium phosphate may include only sodium iron pyrophosphate, sodium iron pyrophosphate, or both sodium iron pyrophosphate and sodium iron pyrophosphate.
[0087] In the embodiments of this application, the sodium ion migration potential barrier in sodium iron pyrophosphate is low, and sodium iron pyrophosphate and sodium iron phosphate can form a heterostructure, thereby improving the sodium ion diffusion capacity inside the positive electrode active material, reducing charge transfer impedance, and improving the power performance of sodium ion battery cells.
[0088] In some embodiments, the dielectric constant D of the cyclic carbonate satisfies: 50 ≤ D ≤ 98.
[0089] D can be 50, 55, 65, 75, 85, 95, 98, or any value within the above range.
[0090] In the embodiments of this application, cyclic carbonates with high dielectric constants are more likely to dissociate from sodium salts, thereby enabling the electrolyte to have higher ionic conductivity and higher sodium ion migration kinetics, thus improving the discharge power of sodium-ion battery cells.
[0091] In some embodiments, cyclic carbonates include propylene carbonate and / or ethylene carbonate.
[0092] Specifically, cyclic carbonates may include only propylene carbonate, only ethylene carbonate, or both propylene carbonate and ethylene carbonate.
[0093] Propylene carbonate has a lower risk of solidification at low temperatures. In addition, it has a lower reduction potential, is less prone to reduction and decomposition, and has stronger chemical stability.
[0094] In the embodiments of this application, the relevant components of the cyclic carbonate can be appropriately decomposed into a film to improve the interfacial stability of the electrode / electrolyte, thereby further taking into account the life performance of the sodium-ion battery cell.
[0095] In some embodiments, the molecular weight M of the chain ester satisfies: 50 ≤ M ≤ 150.
[0096] M can be 50, 70, 90, 110, 130, 150, or any value within the above range.
[0097] In the embodiments of this application, when the molecular weight of the chain ester is within the above range, the chain ester can have a lower viscosity, thereby improving the migration kinetics of sodium ions and increasing the discharge power of sodium-ion battery cells.
[0098] In some embodiments, the chain esters include chain carbonates and / or chain carboxylic acid esters.
[0099] Specifically, a chain ester may include only chain carbonates, only chain carboxylic esters, or both chain carbonates and chain carboxylic esters.
[0100] In the embodiments of this application, the relevant components of the chain ester can further enhance the sodium ion migration kinetics under low temperature conditions, thereby improving the low-temperature discharge power of sodium ion battery cells.
[0101] In some embodiments, the chain carbonate includes at least one of the following: dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl isopropyl carbonate, methyl butyl carbonate, ethyl propyl carbonate, dipropyl carbonate, and dibutyl carbonate.
[0102] In some embodiments, the chain carboxylic acid ester includes at least one of the following: methyl acetate, ethyl acetate, ethyl propionate, methyl formate, ethyl formate, methyl propionate, propyl propionate, ethyl butyrate, and propyl acetate.
[0103] In some embodiments, the sodium-ion battery cell 5 further includes: a housing, which is a hollow structure with an opening, and the electrolyte, negative electrode 51 and positive electrode 53 are housed within the housing; and a top cover that closes the opening.
[0104] [Positive electrode plate]
[0105] The positive electrode includes a positive current collector and a layer of positive active material disposed on the positive current collector. The positive electrode can be the aforementioned positive electrode 53.
[0106] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0107] In some embodiments, the positive electrode active material layer may employ positive electrode active materials known in the art for use in batteries. As an example, the positive electrode active material may include at least one of the following: sodium transition metal oxides, polyanionic compounds, and Prussian blue compounds. However, this application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more.
[0108] In some embodiments, the transition metal in the sodium transition metal oxide can be at least one selected from Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. For example, the sodium transition metal oxide is Na. x MO2, where M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, and 0 < x ≤ 1.
[0109] In some embodiments, the polyanionic compound may be a sodium ion, a transition metal ion, or a tetrahedral (YO4) compound. n- A class of compounds with anionic units. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce; Y can be at least one of P, S, and Si; n represents (YO4). n- The valence state. Polyanionic compounds can also have sodium ions, transition metal ions, or tetrahedral (YO4) ions. n- A class of compounds containing anionic units and halide anions. Transition metals may include at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce; Y may include at least one of P, S, and Si, where n represents (YO4). n- The valence state; halogens can include at least one of F, Cl, and Br. Polyanionic compounds can also have sodium ions, tetrahedral (YO4) valence states. n- Anionic unit, polyhedral unit (ZO) y ) m+And a class of compounds with optional halide anions. Y can include at least one of P, S, and Si, and n represents (YO4). n- The valence state; Z represents a transition metal, which may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce, and m represents (ZO). y ) m+ The valence state; halogens can include at least one of F, Cl, and Br. Examples of polyanionic compounds include NaFePO4, Na3V2(PO4)3 (sodium vanadium phosphate, abbreviated as NVP), Na4Fe3(PO4)2 (P2O7), NaM'PO4F (M' includes one or more of V, Fe, Mn, and Ni), and Na3(VO4) y )2(PO4)2F 3-2y At least one of (0≤y≤1).
[0110] In some embodiments, Prussian blue compounds may contain sodium ions, transition metal ions, and cyanide ions (CN). - A class of compounds. Transition metals include at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. Prussian blue compounds are, for example, Na. a Me b Me' c (CN)6, wherein Me and Me' each independently include at least one of Ni, Cu, Fe, Mn, Co and Zn, 0 < a ≤ 2, 0 < b < 1, 0 < c < 1.
[0111] In some embodiments, the positive electrode active material layer may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.
[0112] In some embodiments, the positive electrode active material layer may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0113] In some embodiments, the positive electrode sheet can be prepared by dispersing the positive active material, conductive agent, binder and any other components in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.
[0114] [Negative electrode plate]
[0115] The negative electrode includes a negative current collector and a layer of negative active material disposed on the negative current collector. The negative electrode can be the aforementioned negative electrode 51.
[0116] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0117] In some embodiments, the negative electrode active material layer includes a negative electrode active material. The negative electrode active material may be any negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, and tin-based materials, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0118] In some embodiments, the negative electrode active material layer may optionally include a binder. As an example, the binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0119] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0120] In some embodiments, the negative electrode active material layer may also optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0121] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material layer, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.
[0122] Electrolyte
[0123] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific limitations on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte may include ethylene fluorocarbonate (FEC) and the lithium-containing compound described in any of the above embodiments. The electrolyte can be the electrolyte described in the above embodiments.
[0124] In some embodiments, the electrolyte includes an organic solvent, a sodium electrolyte salt, and optional additives. The types of organic solvent, sodium electrolyte salt, and additives are not specifically limited and can be selected according to requirements.
[0125] In some embodiments, as examples, the electrolyte salt includes, but is not limited to, NaPF6, Na[(FSO2)2N, Na[(CF3SO2)2N], NaClO4, NaBCl4, NaSO3CF3, and At least one of Na(CH3)C6H4SO3. The above electrolyte salts can be used alone, or two or more can be used simultaneously.
[0126] In some embodiments, as examples, the organic solvent includes, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), methyl ethyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE). One of the above organic solvents may be used alone, or two or more may be used simultaneously. Optionally, two or more of the above organic solvents may be used simultaneously.
[0127] In some embodiments, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0128] In some embodiments, as examples, the additives include, but are not limited to, at least one of fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), vinyl sulfate (DTD), propylene sulfate, vinyl sulfite (ES), 1,3-propanesulfonate lactone (PS), 1,3-propenesulfonate lactone (PST), sulfonate cyclic quaternary ammonium salts, succinic anhydride, succinic anhydride (SN), adiponitrile (AND), tris(trimethylsilane) phosphate (TMSP), and tris(trimethylsilane) borate (TMSB).
[0129] The electrolyte can be prepared according to conventional methods in the art. For example, an organic solvent, a sodium electrolyte salt, and optional additives can be mixed evenly to obtain an electrolyte. There are no particular restrictions on the order of addition of the materials; for example, the sodium electrolyte salt and optional additives can be added to the organic solvent and mixed evenly to obtain an electrolyte; or, the sodium electrolyte salt can be added to the organic solvent first, and then the optional additives can be added to the organic solvent and mixed evenly to obtain an electrolyte.
[0130] [Isolation membrane]
[0131] In some embodiments, the battery cell also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.
[0132] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0133] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.
[0134] In some embodiments, the battery cell may include an outer packaging. This outer packaging can be used to encapsulate the electrode assembly and electrolyte described above.
[0135] In some embodiments, the outer packaging of the battery cell can be a rigid shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the battery cell can also be a flexible package, such as a pouch. The material of the flexible package can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0136] This application does not impose any particular limitation on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 2The sodium-ion battery cell 5 is an example. The sodium-ion battery cell 5 may include a housing. A positive electrode, a negative electrode, and a separator can be formed into an electrode assembly using a winding or stacking process. The electrode assembly is encapsulated within the housing. The sodium-ion battery cell 5 may contain one or more electrode assemblies, which can be selected by those skilled in the art according to specific practical needs.
[0137] In some embodiments, sodium-ion battery cells can be assembled into battery modules, and the number of sodium-ion battery cells contained in a battery module can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery module.
[0138] Figure 3 This is battery module 4, used as an example. (See reference...) Figure 3 In battery module 4, multiple sodium-ion battery cells 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple sodium-ion battery cells 5 can be fixed in place using fasteners.
[0139] Optionally, the battery module 4 may also include a housing with a receiving space in which multiple sodium-ion battery cells 5 are received.
[0140] In some embodiments, the battery modules described above can also be assembled into a battery device. The number of battery modules contained in the battery device can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery device.
[0141] Figure 4 and Figure 5 This is battery device 1 as an example. (See reference...) Figure 4 and Figure 5 The battery device 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper box 2 and a lower box 3, the upper box 2 covering the lower box 3 to form a closed space for accommodating the battery modules 4 and / or sodium-ion battery cells 5. The multiple battery modules 4 may be arranged in any manner within the battery box.
[0142] In addition, this application also provides an electrical device, which includes at least one of the battery cell, battery module, or battery device provided in this application. The battery cell, battery module, or battery device can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0143] As the electrical device, a single battery cell, a battery module, or a battery can be selected according to its usage requirements.
[0144] Figure 6 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of individual battery cells, a battery device or battery module can be used.
[0145] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a single battery cell as their power source.
[0146] In some implementations, the sodium-ion battery cell or battery device is powered by a start-stop power supply for an electrical device.
[0147] Specifically, the power supply for starting and stopping electrical devices may include the sodium-ion battery cells described in the above embodiments and / or battery devices containing the sodium-ion battery cells described in the above embodiments.
[0148] [Example]
[0149] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0150] Example 1
[0151] (1) Preparation of negative electrode sheet
[0152] Hard carbon (negative electrode active material), acetylene black (conductive agent), styrene-butadiene rubber (SBR) (binder), and sodium carboxymethyl cellulose (CMC-Na) (thickener) were mixed and homogenized in a weight ratio of 90:4:4:2 to obtain a negative electrode film slurry. This negative electrode active material slurry was then coated onto a negative electrode current collector and dried in an oven at 100°C, controlling the water content to be less than 150 ppm, to obtain the negative electrode sheet.
[0153] (2) Preparation of positive electrode sheet
[0154] The positive electrode active material (a composite of Na4Fe3(PO4)2P2O7 and Na2FeP2O7), the conductive agent acetylene black, and the binder polyvinylidene fluoride were mixed in a weight ratio of 90:5:5 in the solvent N-methylpyrrolidone (NMP) and stirred thoroughly to prepare the positive electrode active material. The positive electrode active material was then uniformly coated onto the positive electrode current collector aluminum foil, followed by drying, cold pressing, and slitting to obtain the positive electrode sheet. The average thickness of the carbon coating material on the positive electrode active material was 3 nm. The thickness of the positive electrode film layer on one side of the positive electrode current collector was 88 μm.
[0155] (3) Separating membrane
[0156] A polyethylene film layer is used as the isolation membrane.
[0157] (4) Electrolyte
[0158] In an argon atmosphere glove box (H2O content <10ppm, O2 content <1ppm), propylene carbonate, dimethyl carbonate, and methyl acetate are mixed, wherein the mass ratio of propylene carbonate, dimethyl carbonate, and methyl acetate is 26:31:26. Then, sodium difluorooxalate borate additive and sodium difluorosulfonamide (NaFSI) salt are added to obtain the finished electrolyte, wherein sodium difluorooxalate borate accounts for 0.5% of the total mass of the electrolyte, and the molar concentration of NaFSI salt in the total electrolyte is 1 mol / L.
[0159] (5) Preparation of battery cells
[0160] The positive electrode, separator, and negative electrode are arranged in the order of "separator—negative electrode—separator—positive electrode," so that the separator acts as a barrier between the positive and negative electrodes. One end of the positive electrode, negative electrode, and two separators is fixed to the discharge roller, and the other end is stacked together and fixed to the winding shaft. A motor is used to rotate the winding shaft to wind the positive electrode, negative electrode, and two separators. After baking, electrolyte injection, and formation, a single battery cell is obtained.
[0161] Examples 2-5
[0162] The difference between Examples 2-5 and Example 1 is that the mass ratio of cyclic carbonates and chain esters is different.
[0163] Comparative Examples 1-2
[0164] The differences between Comparative Examples 1-2 and Example 1 are as follows: the thickness of the carbon coating material of the positive electrode active material is different, the thickness of the positive electrode film layer on one side of the positive electrode current collector is different, the electrolyte does not contain cyclic carbonates and difluorooxalate borate compounds, and the mass percentage of chain esters in the electrolyte is different.
[0165] The specific parameters of the battery cells in Examples 1-5 and Comparative Examples 1-2 are shown in Table 1 below.
[0166] Table 1: Specific parameters of Examples 1-5 and Comparative Examples 1-2
[0167] In addition, the battery cells in Examples 1-5 and Comparative Examples 1-2 were subjected to performance tests. The test results are shown in Table 2 below.
[0168] Table 2: Performance test results of Examples 1-5 and Comparative Examples 1-2
[0169] As shown in Examples 1-5 and Comparative Examples 1-2, compared to Comparative Examples 1-2, in Examples 1-5, the sodium-ion battery cells exhibit higher cycle capacity retention and high-temperature storage capacity retention. The sodium-ion battery cells also show a higher minimum discharge voltage after 10 seconds of high-rate discharge at low temperature and low SOC. This indicates that when a positive electrode sheet with a relatively thin positive electrode film and carbon-coated sodium phosphate is combined with an electrolyte containing additives including cyclic carbonates, chain esters, and difluorooxalate borate compounds, the internal impedance of the positive electrode sheet and the positive electrode / electrolyte interface impedance can be reduced, while further minimizing side reactions between the phosphate and the electrolyte. This improves the lifespan of the sodium-ion battery cells while maintaining high-power discharge performance at low temperatures. Furthermore, as shown in Examples 1-5, when the mass ratio of cyclic carbonates to chain esters and the mass percentage of cyclic carbonates and chain esters in the electrolyte are within the ranges of Examples 1, 3, and 4, the sodium-ion battery cells exhibit superior discharge power at low temperature and low SOC. This also demonstrates the effect of the mass ratio of cyclic carbonates to chain esters on discharge power.
[0170] Examples 6-9
[0171] The difference between Examples 6-9 and Example 1 is that the mass percentage of difluorooxalate borate compound in the electrolyte is different.
[0172] Comparative Example 3
[0173] The difference between Comparative Example 3 and Example 1 is that the electrolyte does not contain difluorooxalate borate compound.
[0174] The specific parameters of the battery cells in Examples 6-9 and Comparative Example 3 are shown in Table 3 below.
[0175] Table 3: Specific parameters of Examples 6-9
[0176] In addition, the battery cells in Examples 6-9 and Comparative Example 3 were subjected to performance tests. The test results are shown in Table 4 below.
[0177] Table 4: Performance test results of Examples 6-9 and Comparative Example 3
[0178] As shown in Examples 1, 6-9, and Comparative Example 3, compared to Comparative Example 3, the sodium-ion battery cells in Examples 1 and 6-9 exhibit higher cycle capacity retention and high-temperature storage capacity retention. This indicates that difluorooxalate borate compound, as an electrolyte additive, can reduce side reactions between the phosphate cathode active material and the electrolyte solvent components, thereby reducing the impact on the capacity decay of the sodium-ion battery and resulting in better lifespan performance for the sodium-ion battery cells. Furthermore, as shown in Examples 1 and 6-9, when the mass percentage of difluorooxalate borate compound in the electrolyte is within the range of Examples 7-8, the sodium-ion battery cells exhibit even better cycle capacity retention and high-temperature storage capacity retention. This also demonstrates the influence of the mass percentage of difluorooxalate borate compound in the electrolyte on the discharge power. It is reasonable to speculate that if the mass percentage of difluorooxalate borate compound is too high, it may not be completely consumed after the film formation process, potentially leading to an increase in the initial impedance of the electrolyte and thus affecting sodium-ion kinetics. Meanwhile, any unconsumed difluorooxalate borate compounds during subsequent discharge may also deplete the active sodium in the electrolyte, leading to a deterioration in lifespan performance.
[0179] Examples 10-11
[0180] The difference between Examples 10-11 and Example 1 is that the thickness of the positive electrode film layer is different on one side of the positive electrode current collector.
[0181] The specific parameters of the battery cells in Examples 10-11 above are shown in Table 5 below.
[0182] Table 5: Specific parameters of Examples 10-11
[0183] In addition, the battery cells in Examples 10-11 above were subjected to performance tests. The test results are shown in Table 6 below.
[0184] Table 6: Performance Test Results of Examples 10-11
[0185] Referring to Examples 1, 10-11, and Comparative Examples 1-2, compared to Comparative Examples 1-2, in Examples 1 and 10-11, when the thickness of the positive electrode film on one side of the positive electrode current collector is within the aforementioned range, the sodium-ion battery cell exhibits a higher minimum discharge voltage after 10 seconds of high-rate discharge under low-temperature, low-SOC conditions. This indicates that a thinner positive electrode film can increase the transport rate of sodium ions in the positive electrode, thereby improving the high-power discharge performance of the sodium-ion battery. Furthermore, referring to Examples 1 and 10-11, when the thickness of the positive electrode film on one side of the positive electrode current collector is within the range of Examples 1 and 11, the sodium-ion battery cell exhibits superior discharge power under low-temperature, low-SOC conditions. This also demonstrates the influence of the thickness of the positive electrode film on the discharge power. It is reasonable to speculate that if the thickness of the positive electrode film is too large, it may affect electrolyte wetting, leading to a slower sodium ion transport rate, which in turn affects sodium ion kinetics and thus the high-power discharge performance of sodium ions. Meanwhile, although a thinner cathode film results in better sodium ion dynamics, it may affect the energy density of sodium-ion batteries.
[0186] Examples 12-15
[0187] The difference between Examples 12-15 and Example 1 is that the average thickness of the carbon coating material of the positive electrode active material is different.
[0188] The specific parameters of the battery cells in Examples 12-15 above are shown in Table 7 below.
[0189] Table 7: Specific parameters of Examples 12-15
[0190] In addition, the battery cells in Examples 12-15 above were subjected to performance tests. The test results are shown in Table 8 below.
[0191] Table 8: Performance Test Results of Examples 12-15
[0192] In conjunction with Examples 1, 12-15 and Comparative Examples 1-2, compared to Comparative Examples 1-2, in Examples 1 and 12-15, when the average thickness of the carbon coating material on the surface of the sodium phosphate is within the aforementioned range, the electronic conductivity of the positive electrode active material can be further improved, and the sodium-ion battery cell exhibits a higher minimum discharge voltage after 10 seconds of high-rate discharge under low-temperature, low-SOC conditions. Furthermore, as shown in Examples 1 and 12-15, when the average thickness of the carbon coating material on the surface of the sodium phosphate is too small, the minimum discharge voltage also decreases. Simultaneously, when the average thickness is too large, the minimum discharge voltage also decreases. However, when the average thickness of the carbon coating material on the surface of the sodium phosphate is within the range of Examples 13 and 14, the sodium-ion battery cell exhibits superior discharge power under low-temperature, low-SOC conditions. Therefore, this demonstrates the influence of the average thickness of the carbon coating material on the surface of the sodium phosphate on the discharge power of the sodium-ion battery, and it can be reasonably inferred that both excessively small and excessively large average thicknesses of the carbon coating material on the surface of the sodium phosphate will affect the high-power discharge performance of the sodium-ion battery.
[0193] Examples 16-17
[0194] The difference between Examples 16-17 and Example 1 is that the components of the chain ester are different.
[0195] The specific parameters of the battery cells in Examples 16-17 above are shown in Table 9 below.
[0196] Table 9: Specific parameters of Examples 16-17
[0197] In addition, the battery cells in Examples 16-17 above were subjected to performance tests. The test results are shown in Table 10 below.
[0198] Table 10: Performance test results of Examples 16-17
[0199] As shown in Examples 1, 16 and 17, compared to Example 1, when the chain ester uses a component with lower viscosity, the sodium-ion battery cell can have a higher cycle capacity retention rate and a higher high-temperature storage capacity retention rate.
[0200] Examples 18-19
[0201] The difference between Examples 18-19 and Example 1 is that the components of the chain ester are different.
[0202] Example 20
[0203] The difference between Example 20 and Example 1 is that the components of the cyclic carbonate are different.
[0204] The specific parameters of the battery cells in the above embodiments 18-20 are shown in Table 11 below.
[0205] Table 11: Specific parameters of Examples 18-20
[0206] In addition, the battery cells in Examples 18-20 above were subjected to performance tests. The test results are shown in Table 12 below.
[0207] Table 12: Performance Test Results of Examples 18-20
[0208] Based on Examples 1 and 20, compared to Example 20, when the cyclic carbonate in Example 1 was propylene carbonate, the sodium-ion battery cell exhibited a higher minimum discharge voltage after 10 seconds of high-rate discharge at low temperature and low SOC, as well as higher cycle capacity retention and high-temperature storage capacity retention. It is reasonable to speculate that the use of ethylene carbonate in Example 20 would make the desolvation process more difficult, thus degrading the discharge power performance of the sodium-ion battery. Furthermore, the ethylene carbonate in Example 20 is more prone to reduction side reactions than the propylene carbonate in Example 1, which may also worsen the lifespan performance of the sodium-ion battery.
[0209] [Testing methods for individual battery cell parameters]
[0210] The battery cells being tested can be either freshly assembled and unformed, or they can be battery cells removed from electrical devices (such as vehicles).
[0211] (1) Testing of discharge power of sodium-ion battery cells under low temperature and low SOC conditions
[0212] Under a 25℃ testing environment, the sodium-ion battery cells prepared above were left to stand for 5 minutes, then charged at a constant current rate of 0.33C to 3.65V, and then charged at a constant voltage rate until the current was less than or equal to 0.05C. After that, they were left to stand for 5 minutes, then discharged at a constant current rate of 0.33C to 1.5V. The discharge capacity of this discharge was recorded as the battery capacity C0. Then, the battery cells were charged at a constant current rate of 0.33C to 0.5C0Ah, adjusting the battery cell capacity to 50% SOC. After standing for 5 minutes, the testing environment temperature was adjusted to -10℃ and left to stand for another 2 hours. Then, they were discharged at a rate of 16.7C for 10 seconds, and the lowest discharge voltage was extracted. The lowest discharge voltage represents the discharge power level.
[0213] (2) Test of capacity retention of sodium-ion battery cells at 25°C
[0214] At 25°C, the sodium-ion battery cell prepared above is charged to 3.65V with a constant current of 0.33C, and then charged with a constant voltage of 3.65V until the current drops to 0.05C. After standing for 5 minutes, it is discharged to 1.5V with a constant current of 1C. This is the first charge / discharge cycle of the battery. The discharge capacity of this cycle is recorded as the discharge capacity C0 of the battery in the first cycle. The above steps are repeated for the same battery. The discharge capacity C1 of the battery after 1000 cycles is recorded. The capacity retention rate after 1000 cycles is (C1 / C0)×100%.
[0215] (3) Test of the rate of change of storage capacity of sodium-ion battery cells at 60℃ high temperature and high pressure
[0216] At 25°C, the sodium-ion battery cells prepared above were left to stand for 5 minutes, then discharged at a constant current rate of 0.33C to 1.5V, and then charged at a constant current rate of 1 / 3C to 3.65V. At 3.65V, they were charged at a constant voltage until the current was less than 0.05C. After standing for 5 minutes, they were discharged at a constant current rate of 0.33C to 1.5V. This discharge capacity is recorded as the battery's initial discharge capacity C0. The battery was then charged at a constant current rate of 0.33C to 3.65V, and then charged at a constant voltage rate of 3.65V until the current was less than 0.05C. It was then stored at 60°C in a constant temperature chamber for 3 months. After this high-temperature storage, the sodium-ion battery was cooled to 25°C and discharged at a constant current rate of 0.33C to 1.5V. This discharge capacity is recorded as the battery's discharge capacity after high-temperature storage C1. The capacity retention rate of a sodium-ion battery after storage at 3.65V at 60℃ is calculated using the following formula: Capacity retention rate (%) of sodium-ion battery after high-temperature storage at 60℃ = (C1 / C0) × 100%.
[0217] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A sodium-ion battery cell, characterized in that, It includes an electrolyte, a negative electrode, and a positive electrode; among which, The positive electrode includes a positive current collector and a positive electrode film layer. The positive electrode film layer is disposed on at least one side of the positive current collector. The thickness L of the positive electrode film layer on one side of the positive current collector satisfies: 55μm≤L≤125μm. The positive electrode film layer includes sodium phosphate and carbon coating material. The carbon coating material covers at least a portion of the surface of the sodium phosphate. The sodium phosphate salt includes sodium iron pyrophosphate and sodium iron pyrophosphate; The average thickness H of the carbon coating material on at least a portion of the surface of the sodium phosphate salt satisfies: 0.4 nm ≤ H ≤ 10 nm; The electrolyte includes cyclic carbonates, chain esters, and additives; The freezing point F of the cyclic carbonate satisfies: -60℃≤F≤38℃; the viscosity N of the chain ester at 25±1℃ satisfies: 0.2mPa.s≤N≤3mPa.s; the mass ratio E of the cyclic carbonate to the chain ester satisfies: 0.14≤E≤1.47; the additive includes difluorooxalate borate compound; and the mass percentage A of the additive in the electrolyte satisfies: 0.05%≤A≤2%.
2. The sodium-ion battery cell according to claim 1, characterized in that, A satisfies: 0.1%≤A≤1%.
3. The sodium-ion battery cell according to claim 1, characterized in that, The mass ratio E of the cyclic carbonate and the chain ester satisfies: 0.14 ≤ E ≤ 0.
93.
4. The sodium-ion battery cell according to any one of claims 1-3, characterized in that, The mass percentage E1 of the cyclic carbonate in the electrolyte satisfies: 0.05 ≤ E1 ≤ 0.
5.
5. The sodium-ion battery cell according to any one of claims 1-3, characterized in that, The mass percentage E2 of the chain ester in the electrolyte satisfies: 0.4 ≤ E2 ≤ 0.
9.
6. The sodium-ion battery cell according to any one of claims 1-3, characterized in that, H satisfies: 2nm≤H≤5nm.
7. The sodium-ion battery cell according to any one of claims 1-3, characterized in that, L satisfies: 55μm≤L≤85μm.
8. The sodium-ion battery cell according to any one of claims 1-3, characterized in that, The Dv50 of the sodium phosphate salt satisfies: 1μm≤Dv50≤18μm.
9. The sodium-ion battery cell according to claim 8, characterized in that, Dv50 satisfies: 7μm≤Dv50≤11μm.
10. The sodium-ion battery cell according to any one of claims 1-3, characterized in that, The cyclic carbonates include propylene carbonate and / or ethylene carbonate.
11. The sodium-ion battery cell according to any one of claims 1-3, characterized in that, The chain esters include chain carbonates and / or chain carboxylic esters.
12. The sodium-ion battery cell according to any one of claims 1-3, characterized in that, The sodium-ion battery cell also includes: The housing is a hollow structure with an opening, and the electrolyte, the negative electrode, and the positive electrode are housed within the housing. A top cover that closes the opening.
13. A battery device, characterized in that, Includes the sodium-ion battery cell according to any one of claims 1-12.
14. An electrical appliance, characterized in that, Includes the sodium-ion battery cell according to any one of claims 1-12 and / or the battery device according to claim 13.
15. The electrical appliance according to claim 14, characterized in that, The sodium-ion battery cell or the battery device serves as the start-stop power source for the electrical device.
Citation Information
Patent Citations
Sodium ion battery
CN118867356A